A study on the contributory factors that lead to the road accidents: a case study at the district of Masjid Tanah, Melaka / Mohammad Shahrul Azmi Mohd Noh and Mohamad Zulhusni Che Kamal - Mohd Noh, Mohammad Shahrul Azmi; Che Kamal, Mohamad Zulhusni (Faculty of Administrative Science and Policy Studies, 2013)
This research was carried out on the contributory factors of road accidents in Masjid Tanah. The purpose of this study is to determine the contributory factors of road accidents i.e. human attitude, road condition and vehicle condition. This study was also to determine the most influential factors to the road accidents. By determining the factors that lead to the road accidents, the society and the government can take some proactive actions to avoid and reduce it. Thus, lot number of life can be saved and not involve in the road accidents. In conducting this research, this study focused on descriptive study as the nature of study. The descriptive study is more describe on the characteristics of variables interest in a situation. The method of convenience sampling was used to set specific types of people who can provide the desired information. About 367 of questionnaires were distributed and were returned and the method used self-development method. Based on the findings, all the variables, road user’s attitude, road condition and vehicle condition has significantly associated to the road accidents.